Kompleksitas Tugas dan TBP Sebagai Pemoderasi Pengaruh Independensi dan Pengalaman Kerja pada Kinerja Auditor - Putri Adnyasuari, A.A; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 23 No 3 (2018)DO - 10.24843/EJA.2018.v23.i03.p11, 2018)
This study aims to analyze the influence of independence and work experience on auditor performance with task complexity and time budget pressure as a moderator variable, the study was conducted on KAP registered in IAPI year 2017. This study used primary data consisting of respondents' answers in the statement in the questionnaire. The study population is all auditors working in KAP in Bali Province. The sample is determined using purposive sampling method. This research uses data analysis technique of MRA with SPSS program. The results of this study show that independence and work experience have a positive effect on auditor performance, the complexity of tasks weakens the influence of independence and work experience on auditor performance, and time budget pressure weakens the influence of independence and work experience on auditor performance. This indicates that the higher independence and work experience of the auditor will improve auditor performance, but with the complexity of the task and time budget pressure will weaken the influence of independence and work experience that will impact on the decrease in auditor performance. Keywords: independence, work experience, task complexity, and time budget pressure